2023
DOI: 10.3390/math11020440
|View full text |Cite
|
Sign up to set email alerts
|

Smart Production System with Random Imperfect Process, Partial Backordering, and Deterioration in an Inflationary Environment

Abstract: In today’s digital age, industrial methods are shifting away from humans and toward machines. We choose automated systems for various jobs related to production systems, such as screening, manufacturing. A smart manufacturing system is one in which machines take the place of humans. Under the influence of inflation, this study proposes a smart production-inventory model with partial backlogging, and an imperfect manufacturing process where the deterioration rate is constant. Every production system, in reality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…They observed that inflation has a positive impact to reduce market disruption. Yadav et al [29] investigated an inventory model for deteriorating items considering smart production process and controllable carbon emission in an inflationary environment. Padiyar et al [30] developed three-echelon integrated inventory model for deteriorating products considering the inflationary environment.…”
Section: Inventory Models With Inflationmentioning
confidence: 99%
“…They observed that inflation has a positive impact to reduce market disruption. Yadav et al [29] investigated an inventory model for deteriorating items considering smart production process and controllable carbon emission in an inflationary environment. Padiyar et al [30] developed three-echelon integrated inventory model for deteriorating products considering the inflationary environment.…”
Section: Inventory Models With Inflationmentioning
confidence: 99%
“…This type of decision problem reveals the need for managers to prioritize, select, and decide which investments should be implemented in the organization to automate the manufacturing system with the aim of increasing system reliability. Thus, the sequencing of machines in business process management, the purchasing of assets to introduce this new paradigm, as well as the enhancement of maintenance planning, can be supported with MCDM/A models [45,64,109,153,156];…”
mentioning
confidence: 99%